Effect of ITO Film on InGaN/GaN MQWs Solar Cell under Low Total-Dose Gamma-Ray Radiation. (1st January 2018) - Shan, Hengsheng; Li, Xiaoya; Lin, Zhiyu; Lv, Ling; Xiao, Ming; Chen, Bin; Bi, Zhen; Du, Jinjuan; Peng, Ruoshi; Xu, Shengrui; Zhang, Jincheng; Hao, Yue
Abstract : An InGaN/GaN multiple quantum wells (MQWs) solar cell deposited with indium-tin oxide (ITO) film was irradiated by Co 60 γ-rays for an accumulated dose of 0.3 Mrad(Si). The short circuit current density, photoelectric conversion efficiency, and maximum external quantum efficiency (EQE) show decreases of 5.67%, 6.20%, and 10.52%, respectively. Moreover, we find that the quality of the material without an ITO layer remains almost unchanged after irradiation. The obvious decrease of ITO transmittance after irradiation proved that the degradation of ITO layer is the main reason of solar cell degradation. Moreover, the analysis of oxygen chemical states in ITO film indicated the increase of oxygen vacancies in ITO leads to the degradation of ITO layer. In addition, the short circuit current density, and photoelectric conversion efficiency measured several hours after irradiation reveal that the degradation can be partially recovered. The reason comes from the partial recovery of ITO layer, which is verified by the increase of ITO transmittance and decrease of oxygen vacancies.